Exposure to Racial Discrimination and Ambulatory Blood Pressure in Women with Type 2 Diabetes. (30th January 2015) - Wagner, Julie; Tennen, Howard; Finan, Patrick; Feinn, Richard; Burg, Matthew M.; Seawell, Asani; White, William B.
Abstract: Diabetes is the only disorder in which women's risk for heart disease exceeds men's. Elevated blood pressure (BP) increases cardiovascular risk in people with type 2 diabetes. Racial discrimination and neuroticism are both associated with BP levels but have not been examined in concert. This study investigated self‐reported racial discrimination, neuroticism and ambulatory BP in women with type 2 diabetes. Thirty‐nine Black and 38 White women completed a race‐neutral version of the Schedule of Racist Events; BP was evaluated using ambulatory monitoring devices. Actigraphy and diaries were used to document times of sleep and wakefulness. Racial discrimination interacted with neuroticism to predict systolic and diastolic BP both while awake and during sleep, after adjustment for covariates. For each, the influence of racist events was stronger at lower levels of neuroticism. Racial discrimination is associated with higher levels of 24‐h BP in diabetic women who are low in neuroticism. Copyright © 2015 John Wiley & Sons, Ltd.